Reliability and accuracy of varicocele videos in YouTube - Dogan, Cagri; Akgul, Haci Murat; Yazici, Cenk Murat; Sahin, Mehmet Fatih; Keles, Anil (Journal of the Pakistan Medical Association, 2022)
Objectives: To evaluate the scientific impact of videos about varicocele on YouTube. Method: A cross-sectional study was conducted at Turkey in September 2020, and comprised YouTube videos related to varicocele. The videos were divided into 2 groups according to their reliability and accuracy using the European Association of Urology Sexual and Reproductive Guidelines 2020. A 5-point modified reliability (DISCERN) tool, Global Quality Score, and Journal of the American Medical Association scores of each video were calculated. The user’s engagements by total views, video-related comments, and “likes” and “dislikes” to the videos were compared. Data was analysed using SPSS 23. Results: Of the 151 videos assessed, 73(48.34%) were included; 36(49.3%) reliable and 37(50.7%) unreliable. All scores were significantly higher for reliable videos (p<0.05). The mean number of views was 108448±90567 for reliable and 392626±895897 for unreliable videos (p=0.044). The rates of “likes” and “dislikes” were similar between the groups, whereas the comment rate was significantly higher for reliable videos (p<0.05). Most of the videos 40(54.8%) were uploaded by medical advertisements or for-profit companies, while those uploaded by universities or professional organisations were 19(26%). Conclusion: Nearly half of the varicocele-related videos on YouTube were unreliable, and the reliability of videos was not directly related to their popularity. Key Words: Social media, Ethics, Misinformation, Varicocele, Internet.